Dendronized Silver Nanoparticles as Bacterial Membrane Permeabilizers and Their Interactions With P. aeruginosa Lipopolysaccharides, Lysozymes, and Phage-Derived Endolysins - Ciepluch, Karol; Skrzyniarz, Kinga; Barrios-Gumiel, Andrea; Quintana, Sara; Sánchez-Nieves, Javier; de la Mata, F. Javier; Maciejewska, Barbara; Drulis-Kawa, Zuzanna; Arabski, Michał (Frontiers in Microbiology, 2019)
The antimicrobial proteins like lysozyme produced by animals or bacteriophage lysins enable to degrade bacterial peptidoglycan (PG) and in the consequence lead to bacterial cell lysis. However, the activity of those enzymes are not satisfactory against Gram-negative bacteria because of outer membrane barrier presence. Therefore, lytic enzymes can be combined with membrane-disrupting agents such as dendritic silver nanoparticles. Nevertheless, the lipopolysaccharide (LPS), especially the smooth type, could be the main hindrance for highly charged nanoparticles to get direct access to bacterial outer membrane and to help lytic enzymes reaching the target (PG). Herein, we investigate the interactions of PEGylated carbosilane dendritic nanoparticles with P. aeruginosa 010 LPS in the presence of lysozyme and KP27 endolysin to find out the main aspects of OM destabilization process. Our results shows that PEGylated dendronized AgNPs overcome LPS barrier and enhance antibacterial effect of endolysin more efficiently than unPEGylated nanoparticles.